Comparison of the neutron and ion irradiation response of nano-oxides in oxide dispersion strengthened materials. Issue 14 (20th July 2015) - Ribis, Joël; Bordas, Eric; Trocellier, Patrick; Serruys, Yves; de Carlan, Yann; Legris, Alexandre
Abstract: Abstract : The Oxide Dispersion Strengthened (ODS) materials are potential candidates as cladding tubes for Sodium-cooled Fast Reactors. The nano-oxides are finely dispersed within the grains and confer excellent mechanical properties to these alloys. Hence, assessing nano-particle stability under irradiation remains crucial to guarantee safe use of these materials. Although neutron irradiation remains a binding and challenging experimental study to conduct, difficulties can be overcome by ion beam processing. Ion beam processing of the ODS material allows to identify the radiation-induced Ostwald ripening as the mechanism governing the nano-particle response under irradiation. The result is the increase in size and a decrease in density of the finely dispersed Y2 Ti2 O7 nano-particles. Under neutron irradiation, radiation-induced Ostwald ripening appears to be less effective since a slight growth of nano-particles is observed. Further, our approach shows that nanoparticle growth kinetics should scale as φ 1/3, φ being the radiation flux. This suggests that the low irradiation flux is at the origin of the slower growth kinetics of the neutron irradiated particles. Both neutron and ion irradiation induce a modification of the nanoparticles/matrix interfaces which are generally flat and sharp prior to irradiation and present steps after irradiation. This could alter the nano-particle coarsening during irradiation.